2014
DOI: 10.1038/srep03778
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Structure of Luminescent Centers in High-Efficiency Ce-doped w-AlN Single Crystal

Abstract: Rare-earth doped wurtzite-type aluminum nitride (w-AlN) has great potential for high-efficiency electroluminescent applications over a wide wavelength range. However, because of their large atomic size, it has been difficult to stably dope individual rare-earth atoms into the w-AlN host lattice. Here we use a reactive flux method under high pressure and high temperature to obtain cerium (Ce) doped w-AlN single crystals with pink-colored luminescence. In order to elucidate the atomic structure of the luminescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 32 publications
0
31
0
Order By: Relevance
“…Figure 1c,d show views along a <110> p direction. These images are the result of summing ten sequentially acquired frames after alignment by cross-correlation12, with no other image processing being applied. These images are from thin, single domain regions of the specimens (Supplementary Figure S1 containing lower magnification images show that the crushed powder SYCO specimens contain at least three, orthogonal domains).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1c,d show views along a <110> p direction. These images are the result of summing ten sequentially acquired frames after alignment by cross-correlation12, with no other image processing being applied. These images are from thin, single domain regions of the specimens (Supplementary Figure S1 containing lower magnification images show that the crushed powder SYCO specimens contain at least three, orthogonal domains).…”
Section: Resultsmentioning
confidence: 99%
“…The characteristic energy range of AlN luminescence is in the UV-blue portions of the spectrum 16 . Study [10] contains a description of Ce-doped AlN single crystal preparation and examination of the luminescence, which, according to the authors, exhibits pink color centers. Blue-violet self-activated luminescence was mentioned 17 .Photonic crystals were fabricated by the authors of [18], which showed luminescence in the deep UV region.…”
Section: Radiative Process In Silicon Carbide and Aluminum Nitridementioning
confidence: 99%
“…To investigate the depth sensitivity of LAI-STEM, we have chosen to study a Ce-doped w-AlN system [47] and the defect structure model that was used is shown in Fig. 5(a).…”
Section: Three-dimensional Point Defect Imagingmentioning
confidence: 99%